Arattupuzha Velayudha Panicker: A Pioneer Social Reformer of Ezhava Community in Kerala - ARYA P (IRJMST, 2018)
Nineteenth century witnessed the emergence of a number of social reformers in Kerala who raised their voice against the caste discrimination. Arattupuzha Velayudha Panicker was one among them, who challenged the assumed supremacy of the savarnas and tried to uplift the avarnas and thereby tried to purify Hindu society. To attain equality in the society he led a series of struggles. But as a pioneer reformer from a backward community, his contributions were not received the proper attention of the scholars. So this study tries to bring light on the unwritten contributions of Arattupuzha Velayudha Panicker.